2014
DOI: 10.1186/bf03351577
|View full text |Cite
|
Sign up to set email alerts
|

2-D georesistivity structure in the central part of the northeastern Japan arc

Abstract: Wide-band (0.002∼20,000 Hz) magnetotelluric measurements (MT) observations have been conducted along three traverses in the central Tohoku district of the northeastern Japan arc at 86 observation sites since 1990 in order to image the electrical resistivity structure. We used the impedance tensors fully corrected for the three-dimensional galvanic distortion effects including static shift effects in order to refine previous 2-D models (discussed in Fujinawa et al., 1997). The subsurface 3-D effects are found t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 36 publications
1
10
0
Order By: Relevance
“…A calculation at any point indicated that the sharp initial rise of the signal is conserved even at a distance of 30 km from the source (see [33, Figure 13]) by assuming electrical conductivity σ = 0.001 Sm −1 (the conductivity is around 0.01 ∼ 0.001 Sm −1 in central Japan [46]). The amplitude decreases by two orders but still can be detected by measurement system having high enough resolving power and S/N ratio, which is the case for the present special borehole measurement system.…”
Section: Homogeneous Diffusion Modelmentioning
confidence: 99%
“…A calculation at any point indicated that the sharp initial rise of the signal is conserved even at a distance of 30 km from the source (see [33, Figure 13]) by assuming electrical conductivity σ = 0.001 Sm −1 (the conductivity is around 0.01 ∼ 0.001 Sm −1 in central Japan [46]). The amplitude decreases by two orders but still can be detected by measurement system having high enough resolving power and S/N ratio, which is the case for the present special borehole measurement system.…”
Section: Homogeneous Diffusion Modelmentioning
confidence: 99%
“…Magnetotelluric observation data are briefly described here (see Fujinawa et al, 1997Fujinawa et al, , 1999. Broadband magnetotelluric data were acquired along six traverses (A, B, C, D, Copy right c The Society of Geomagnetism and Earth, Planetary and Space Sciences (SGEPSS); The Seismological Society of Japan; The Volcanological Society of Japan; The Geodetic Society of Japan; The Japanese Society for Planetary Sciences.…”
Section: Datamentioning
confidence: 99%
“…The remote reference technique (Gamble et al, 1979) was adopted in order to minimize the effects of noise. Several steps to improve data quality were taken, besides the remote reference technique, such as smoothing the impedance tensor in the frequency domain through the 1-D Bostic model.…”
Section: Datamentioning
confidence: 99%
See 2 more Smart Citations